Gender Based Variation in Birth Outcomes in Terms of Mortality and Morbidity in Lumbini Province, Nepal - Lamichhane, Bikash; Darlami, Radha; Bhattarai, Stuti; Pokhrel, Bishal; Gurung, Prashansa (Nepal Journal of Health Sciences, 2026)
Introduction: Gender is a crucial factor in preterm outcomes and should be taken into account when designing clinical and experimental research. Fetal sex is an important risk factor for stillbirths and early neonatal mortality. Objective: To assess the gender based variation in birth outcomes in terms of mortality and morbidity.Methods: A descriptive cross-sectional study was conducted at maternity ward and NICU of Rapti Academy of Health Sciences. Records of 2326 neonates born from 17th July 2023 to 16th July 2024 were consecutively sampled and retrieved. Frequencies, mean and median of variables were calculated and for inferential analysis chi square test was used. Results: Out of 2326 deliveries, majority of the women (66.3%) were aged 20-30 years. Most deliveries (91.5%) occurred at 37- 42 weeks, predominantly via normal vaginal delivery (66.8%). Of 2340 newborns, 55.1% were male, and 97.2% were live births, with 88% weighing 2500- 4000 grams. Neonatal morbidity was observed in 8.4% of cases, mainly caused by sepsis (29.6%) and jaundice (23.5%), among them almost two third (59.7%) were male. Only one male newborn had birth defect. Birth weight showed a significant association with gender (p=0.045).Conclusion: This study found female neonates had higher rates of low birth weight, while male infants comprised 59.7% of morbidity cases. The findings emphasize the importance of antenatal monitoring for at risk pregnancies, particularly to address low birth weight in newborn, and targeted interventions for sepsis and jaundice as leading causes of morbidity. Multicentre studies are recommended to enhance the generalizability of these findings.